578. INO-4800 DNA Vaccine Induces Neutralizing Antibodies and T cell Activity Against Global SARS-CoV-2 Variants. (4th December 2021) - Andrade, Viviane M; Christensen-Quick, Aaron; Agnes, Joseph; Tur, Jared; Reed, Charles C; Kalia, Richa; Marrero, Idania; Elwood, Dustin; Schultheis, Katherine; Purwar, Mansi; Reuschel, Emma; McMullan, Trevor; et al.
Abstract: Background: Global surveillance has identified emerging SARS-CoV-2 variants of concern (VOC) associated with increased transmissibility, disease severity, and resistance to neutralization by current vaccines under emergency use authorization (EUA). Here we assessed cross-immune responses of INO-4800 vaccinated subjects against SARS-CoV-2 VOCs. Methods: We used a SARS-CoV-2 IgG ELISA and a pseudo neutralization assay to assess humoral responses, and an IFNγ ELISpot to measure cellular responses against SARS-CoV-2 VOC in subjects immunized with the DNA vaccine, INO-4800. Results: IgG binding titers were not impacted between wild-type (WT) and B.1.1.7 or B.1.351 variants. An average 1.9-fold reduction was observed for the P.1 variant in subjects tested at week 8 after receiving two doses of INO-4800 (Figure 1a). We performed a SARS-CoV-2 pseudovirus neutralization assay using sera collected from 13 subjects two weeks after administration of a third dose of either 0.5 mg, 1 mg, or 2 mg of INO-4800. Neutralization was detected against WT and the emerging variants in all samples tested. The mean ID50 titers for the WT, B.1.1.7, B.1.351 and P.1. were 643 (range: 70-729), 295 (range: 46-886), 105 (range: 25-309), and 664 (range: 25-2087), respectively. Compared to WT, there was a 2.1 and 6.9-fold reduction for B.1.1.7 and B.1.351, respectively, while there was no difference between WT and the P.1 variant (Figure 1b). Next, we compared cellular immune responses to WT and SARS-CoV-2 Spike variants elicited by INO-4800 vaccination. We observed similar cellular responses to WT (median = 82.2 IQR = 58.9-205.3), B.1.1.7 (79.4, IQR = 38.9- 179.7), B.1.351 (80, IQR = 40.0-208.6) and P.1 (78.3, IQR = 53.1-177.8) Spike peptides (Figure 2). Conclusion: INO-4800 vaccination induced neutralizing antibodies against all variants tested, with reduced levels detected against B.1.351. IFNγ T cell responses were fully maintained against all variants tested. Disclosures: Viviane M. Andrade, PhD, Inovio Pharmaceuticals Inc. (Employee) Aaron Christensen-Quick, PhD, Inovio Pharmaceuticals, Inc (Employee) Joseph Agnes, PhD, Inovio (Employee, Shareholder) Jared Tur, PhD, Inovio (Employee) Charles C. Reed, PhD, Inovio Pharmaceuticals (Employee, Shareholder) Richa Kalia, MS, Inovio Pharmaceuticals (Employee, Other Financial or Material Support, I have stock options with Inovio Pharmaceuticals as an employee.) Idania Marrero, MD, PhD, Inovio Pharmaceuticals (Employee, Shareholder) Dustin Elwood, PhD, Inovio Pharmaceuticals (Employee) Katherine Schultheis, MSc, Inovio Pharmaceuticals (Employee) Emma Reuschel, PhD, Inovio Pharmaceuticals (Employee) Trevor McMullan, MSc, Inovio (Shareholder) Patrick Pezzoli, BS, Inovio (Employee) Kimberly A. Kraynyak, PhD, Inovio Pharmaceuticals (Employee, Other Financial or Material Support, Stock options) Albert Sylvester, MS, Inovio (Employee, Shareholder) Mammen P. Mammen Jr., MD, Inovio Pharmaceuticals (Employee) J Joseph Kim, PhD, Inovio (Employee) David Weiner, PhD, Inovio (Board Member, Grant/Research Support, Shareholder, I serve on the SAB in addition to the above activities) Trevor R. F. Smith, PhD, Inovio (Employee, Shareholder) Stephanie Ramos, PhD, Inovio Pharmaceuticals (Employee) Laurent Humeau, PhD, Inovio Pharmaceuticals (Employee) Jean Boyer, PhD, Inovio (Employee) Kate Broderick, PhD, Inovio (Employee)